Role-playing game to promote the participation of key stakeholders in the livestock sector and catalog of fodder trees in Mesoamerica - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
In the process of validating, printing, translating to English and disseminating with the livestock sector.